Utilización de saccharomyces cerevisiae como suplemento alimenticio para terneras de tres a cuatro meses de edad - Méndez Campoverde, Lorena Alexandra (2008)
The present work consisted on the use of Saccharomyces cerevisiae like nutritious supplement in veals from three to four months of age, he/she was carried out in the country property Cabuyas, road to San Jacinto, Canton Santa Rosa. You begins from Julio to September of the 2007, and haved the following objectives: 1. To determine the appropriate quantity of Saccharomyces cerevisiae like nutritious supplement for veals from three to four months of age; 2. To establish the gain of weight in the veals during the following two months; 3. To analyze relationship Cost - Benefit. I take an initial weight in the day 0 and of there every 15 days until completing the 60 days of the work, each group remained in its corral with its established and alone diet they left in the day of its pesaje. It was determined that better results were obtained when adding 3 g from yeast to the group B. In the same way he/she settled down that the group B the one that better increment of weight obtained was, although the group C also had a slight increase, but it was not as significant as the group before mentioned. The obtained economic benefit was good, although it didn't equal the parameters gotten in other rehearsals; however the reached percentage (11,64%) it constitutes an item anything worthless for our cattlemen.